Chlamydia trachomatis in hydrocele fluid. Issue 6 (December 1997) - Satpathy, G; Mohanty, S; Pani, S P; Panda, S K
Abstract : OBJECTIVE: To determine the presence of Chlamydia trachomatis in hydrocele fluid. METHODS: 90 male patients with hydrocele of tunica vaginalis from an endemic area for bancroftian filariasis were investigated for the presence of Chlamydia trachomatis in their hydrocele fluids. C trachomatis antigen detection tests-a direct immunofluorescence assay and an enzyme immunoassay along with polymerase chain reaction assay for amplification of a 517 bp fragment of C trachomatis endogenous plasmid-were used in this study. The patients were also tested for the presence of microfilaria in their hydrocele fluids and night blood. Histopathological examination was carried out to detect adult filarial worm in tunica vaginalis testes. RESULTS: Eight (8.88%) patients had chlamydia antigen in the hydrocele fluids; C trachomatis plasmid sequences could be amplified from five of these. Seven (7.77%) patients had microfilaria in the hydrocele fluids, three of them having adult worm in tunica vaginalis. CONCLUSION: C trachomatis infection might be associated with hydrocele in some of these patients.